Selection of construction solutions and materials to improve indoor environmental quality of buildings - Silva, Sandra Monteiro (2011)
The energy efficiency of buildings is nowadays one of the main concerns of the construction market. But, Indoor Environmental Quality of Buildings (IEQ) should not be disregarded. To achieve an adequate quality of buildings it is necessary to consider a set of aspects that are interconnected and influence each other, not always in a favourable way. The selection of the most suitable construction solution and materials for the building elements must consider its contribution for the IEQ (thermal and acoustic comfort, daylight conditions and the indoor air quality) inside the buildings, its energy efficiency and its environmental impact (considering the embodied energy, for example), but also the weight of the solution and its effect on the structural project of the building. The solutions adopted in buildings, usually, only optimize no more than one of the necessary comfort requirements. In many cases, the best solutions to accomplish different comfort requirements are not compatible, especially in what concerns natural ventilation and lighting strategies and the acoustic and thermal performance. So, it is necessary to have an integrated approach to ensure the best overall behaviour taking into account all of the, sometimes incompatible, comfort and energy efficiency requirements. In this work the use of a multi-criteria analysis, to balance all these aspects on the design phase, in order to assist the designer in the selection of construction solutions and materials will be presented. The selection of the most adequate construction solutions will increase the buildings IEQ, energy performance and also its environmental impact.